Managing the multigenerational librarian workforce - Holder, Sara, 1967-; Lannon, Amber (Chandos information professional series., 2018)
"Managing the Multigenerational Librarian Workforce examines how libraries are undergoing a massive shift in their workforce. As baby boomers retire, an influx of Gen Y and millennials has taken their place. This book presents the differences that generational groups bring to the workforce, along with a working mindset that has been shaped, at least in part, by when they were educated and spent their formative early-career years. For the librarian manager, it is important to understand the needs and perspectives of various generations and the career stages they are in if they are to effectively manage the library. Presents information on the reality of multigenerational workforces in libraries and how to manage expectations and differences. Addresses the challenges of having many kinds of staff, some of which will stem from differing generational perspectives. Provides practical advice on how to recognize different perspectives and how to work with librarians in different career phases and from different generations"--